A bibliometric study of technological proficiency in higher education - Ahmad, Shoeb; Jalagat, Jr., Revenio; Alfalih, Abdulaziz Abdulmohsen; Mirza, Adil (Humanities, Arts and Social Sciences Studies, 2025)
The study of technological proficiency is a key concern within a nation's educational and social programs. Throughout their academic journey, ranging from primary through secondary education and afterwards in higher education, students cultivate and enhance a diverse range of abilities, including technology proficiency. Information technology has changed the way businesses and higher education institutions work and the strategies they use. Colleges and universities worldwide are spending a lot of money on IT resources for students and faculty. Hence, this study investigates the trend of studies conducted in the field from 2000–2023 using bibliometric analysis. The bibliometric data generated contains 831 documents and was analyzed using VOSViewer software. Highlights of the findings revealed that the highest number of documents was published in 2020–2023, they were mostly sourced from journals, and top institutions performing research were from the USA, Australia, Israel, England, and Mexico. Antonella Nuzzaci was the author with the most publications, and the journals with most articles in the field were the Interdisciplinary Journal of e-Skills and Lifelong Learning Education, and Information Technologies. The results of co-occurrences based on Total Link Strength revealed keywords such as universities, internet, online learning, technology, and curriculum. The most cited documents were published from 2000–2005, and the most cited journals are Education and Information Technologies, Small Business Economics, and TechTrends. The trend of research on technological proficiency in higher education from 2000–2023 serves as reliable data to consider for further studies related to the field and for references and literature. The findings add value to current studies or topics of interest.